Social Finance and Financing Social Enterprises: An Islamic Finance Prospective - Biancone, Paolo Pietro; Radwan, Maha (European Journal of Islamic Finance, 2019)
Enterprises that have a dual objective of generating positive social impact and financial economic benefit turned to be vital with the increased level of poverty and other major social problems accompanied with limited public spending. The growth and development of social impact enterprises is fundamental for all economies and financing them is a challenging issue where they struggle to accessing finance. Traditional financial instruments are difficult to access especially after the recent financial crisis due to that social enterprises face high risk regarding generating profit, problems of governance model, and lacks of performance measurement valuations especially when it comes to measuring social value. On the other hand, Islamic finance has experienced progressive growth in the last years and could play significant role not only limited to Muslims but also for Non-Muslim countries. Advances in Islamic Finance and Social Finance demonstrate an increasing global attention for finding alternative ways of financing and creating value in the society since both of them have similar ethical dictates. Sharia that regulates all Islamic financial instruments and investments and its screening methodology prohibits unethical businesses and practices that are similar to the negative screening methodology adopted by the socially responsible investment which make both of them connected to Social Finance. This paper is exploratory in nature and argues that Islamic finance could be a viable potential alternative with its diversified instruments for financing social impact enterprises. The paper provides insights for researchers, decision makers, and practitioners of how Islamic finance provide valid financing tools for social finance through mobilizing private funds allocated from investors who seeks investments that generate both social and economic value.